Tangled = Rapunzel - Greno, Nathan; Howard, Byron (Walt Disney Pictures, 2010)
The magically long-haired Rapunzel has spent her entire life in a tower, but now that a runaway thief has stumbled upon her, she is about to discover the world for the first time, and who she really is.
3-6.
K-3.
Language : Turkish, English.
Subtitle : Turkish, English.
Keywords: Movie -- animated films; Movie -- based on tale; Movie -- Kids/Family.